A personal history of the CAMPATH-1H antibody. - Waldmann, H (2002)
The recent licensing of CAMPATH-1H (alemtuzumab) for the treatment of patients with refractory chronic lymphocytic leukemia has been the culmination of a long journey. This success is in large part due to the persistence, dedication, and commitment of a large number of academic collaborators. The first breakthrough was the identification of CAMPATH-1M, an isotype directed against CD52, and extremely efficient at lysing target cells in the presence of human complement, but limited in vivo by the rate of complement biosynthesis. The search for a monoclonal antibody that was more efficient in vivo found the rare class-switching variant CAMPATH-1G, which is able to kill target cells by antibody-dependent cell-mediated cytotoxicity. Construction of the humanized form of the antibody, CAMPATH-1H, and the development of resources to manufacture clinical-grade material, further expedited many studies across the world in leukemia and lymphoma as well as in marrow transplantation, autoimmune disorders, and kidney transplantation. Such studies have taught us a lot about the diseases themselves, as well as offering the prospect of harnessing immunological tolerance processes to facilitate a whole new approach to immunosuppression.